Efektivitas ekstrak buah Beta vulgaris l. (buah bit) dengan berbagai fraksi pelarut terhadap Mortalitas larva Aedes aegypti - Mutiara Widawati; Heni Prasetyowati (ASPIRATOR - Journal of Vector-borne Disease Studies, 2013)
Dengue vector control is mostly done by using plant-based insecticides. Insecticides from the vegetable and fruit extracts of the leaves of plants that contain compounds alkaloids, saponins, flavonoids, tannins, triterpenoids, and polyphenols can be used as an alternative to naturally control Ae. aegypti. The purpose of this study was to determine the effectiveness of the B. vulgaris L. extract larvacide against larvae of Ae. aegypti. The materials that been used was B. vulgaris L. fruit parts which was milled and dried to become a powder form. 800 g of dry powder was extracted by 70% methanol by percolation method with occasional stirring for 3 days. The extract was concentrated using an evaporator. 60 g remaining residue was dissolved in distilled water and re-extracted with diethyl ether, chloroform, and ethyl acetate. Each fraction extract was dried with anhydrous sodium sulfate and the solvent was distilled. The extract was tested qualitatively to determine the content of secondary metabolites. Larvacide test performed by dissolving each extracts in dimetilsulphoxide (DMSO) at concentrations of 0.1, 0.5 and 1%. The larvae used was larval of Ae. aegypti age of seven days. Death larvae counted every day for seven days to determine the effect of the contact. Tests carried out at a temperature of 27±1° C by immersing 25 larvae at each concentration of the extract with 50 mL volume and three replications was performed. The data obtained were analyzed further with different test. The results showed that fruit extract contains flavonoids, alkoloid, sterols, triterpenes, saponins and tannins. Highest mortality happened which was 82.5% and the lowest mortality happened with a concentration of 0.1% diethyl ether extract fraction. The extracts that are dissolved in various solvent fractions have not been effective as a larvacide until the highest concentration which was 1%. Methanol and polar solvent extracts of the fruit has a larvacide potency a bit higher than other solvents.